Environmental Risk Assessment as a tool to support the Free, Prior and Informed Consultation of the indigenous peoples of Ecuador - Durango-Cordero, Juan (2022)
This study discusses the importance of including risk assessment within the process of free, prior and informed consultation and prior consent, within the bidding processes of industrial, mining or oil activities, and within indigenous territories in Ecuador. Spatial risk assessment is a support tool for decision making prior to any industrial activity in its territory. To achieve this objective, we use a logically deductive approach to create a legal and operational conceptual framework that follows the following steps: 1) Compilation of historical evidence of some legal cases brought within the Inter-American Human Rights System, between communities and governments in the region, 2) conceptualization of human rights vulnerabilities and their potential for environmental degradation during these human activities; 3) Introduce legislation to integrate environmental risk research into the free, prior and informed consultation, considering the possibility of looking for consensus when risks are considered high, in order to reduce and mitigate socio-environmental risks on these ancestral territories